MENGHARGAI DAN MENGHORMATI SUATU PERBEDAAN DAN KETIDAKSAMAAN DALAM NEGARA DEMOKRASI (SUATU HARAPAN) - ., Suyatno (PKn Progresif, 2006)
Indonesia is built on various race, tribes, religion and cultural basic. For maintaining region  unity needs positif sense from all elements for respecting and appreciating each difference in building religious, humanity, unity, democratic, justice, welfare, autonomous good and clean goverment.